Medical and social aspects of population safety and protection in wars and armed conflicts (One Health & Risk Management, 2021)
Introduction. The concept of war and armed conflict refers to any confrontation in order to provide contradiction resolution between states, peoples, and social groups by means of armed forces. The war and military conflicts are divided into regional and global ones, depending on their aims, scale and intensity.  Actually, these are a policy continuity of specific powers regardless of the reasons of their emergence (political, economic, territorial or religious). During the conflicts, both overall human and health losses among the participating military personnel, as well as overall human and health losses among the civilian population (collateral losses) occur.Material and methods. The purpose of the present study review was to highlight both medical and social aspects, as well as the risk management related to wars and military conflicts worldwide, especially in Afghanistan, the Dniester, Chechnya, Georgia, Ukraine, and North Karabakh. The studied bibliographic sources provided extensive data on the wars and armed conflicts worldwide and their consequences on the civilian population from these impacted areas. The study was conducted by using historical and descriptive methods based on the keywords, which emphasize the medical, social and economic impact of the presented issue.Results. The study showed that the medical and social aspects of wars and armed conflicts are determined both by direct or indirect action of the destructive nature of weapons, military equipment, and the precarious sanitary-epidemiological situation occurring within the affected localities and regions, followed by total or partial damage of community social infrastructure, healthcare facilities, as well as uncontrolled mass migration of the civilian population.The main directions regarding the security and protection of the civilian population during wars and military conflicts are aimed at providing medical assistance according to the medical guidelines, evacuation from high-risk areas, organizing and performing sanitary-hygienic and anti-epidemic measures among the civilian population and refugees, who are placed in camps or specific areas provided by the host government.These specific measures are carried out according to international convention requirements on the protection and safety of civilians during war and military conflicts. It is essential to plan, coordinate and interact these means with military, civilian, medical-military and health care bodies, as well as with international organizations, namely the United Nations and the World Health Organization.Conclusions. Despite that, national and international communities are actively taking part in maintaining world peace, the wars and military conflicts continue to be a current global issue. Thus, the safety and protection of the civilian population must be a priority for local, regional and international organizations, considering previous experience gained from wars and armed conflicts.
Keywords: war; armed conflict; population; social and medical risks.